PENGEMBANGAN MULTIMEDIA TERHADAP PENGAJARAN PENDIDIKAN AGAMA KRISTEN PADA MASA PANDEMI COVID-19 - Santi Mali (STAK Anak Bangsa, 2021)
AbstractThis article aims to produce multimedia learning for Christian religious education in the midst of the COVID-19 pandemic, which is suitable for use as a learning resource. Aritkel for the development of multimedia Christian religious learning is viewed from the aspect of the ease of operation of the product, the aspect of the ease of the product to learn its contents, and the aspect of attractiveness. The average field trial results show that the multimedia learning of Christianity in terms of the ease of operation of the product, the aspect of the ease with which the product can be studied, and the aspect of attractiveness of the display is considered